Impact of access to microfinance services on farm households’ income in Iringa region, Tanzania - Mapesa, Haruni Jeremia (Sokoine University of Agriculture (SUA), 2023)
A thesis submitted in fulfilment of the requirements for the degree of Doctor of philosophy of Sokoine University of Agriculture Morogoro, Tanzania.